An overlooked treatise in Greek political thought: An essay on 2 Maccabees as a Hellenistic politico-theological manifest1. (December 2019) - Mendels, Doron
This essay does not dwell yet again on traditional issues associated with 2 Maccabees usually discussed through a Jewish lens by dozens of modern scholars. It also does not view the book within its traditional Jewish Hellenistic "Sitz im Leben, " with its self-evident Hellenistic-Jewish reading audience, and its aim is neither to draw a distinction between Greek topoi and biblical motifs nor to discuss its values as an historical text. Rather, the article assumes a pagan reading publicum alongside a Jewish Hellenistic one that, in contradistinction with its Jewish audience, could easily see in 2 Maccabees a standard narrative of a life in a Greek polis under foreign rule, where the "ancestral constitution" plays a significant role, so typical of Greek poleis from the classical period (Delian league) through the Hellenistic era (Macedonian Ptolemaic and Seleucid empires). Reading the book as a Greek would have can give us new insights concerning its socio-political and theological message (independently of its Jewish one). The article reconstructs a politeia as a learned Greek would have done. The book can actually be read as a reflection, or rather a microcosmos of the second century B.C.E. in the Greek sphere during the Hellenistic period. The overall message of the book emerges different than that broadcasted to the Hellenistic Jews, and constitutes a rich mine of theoretical information about the relationship between a subject city and an empire.